Anesthetic concentration of eugenol in angelfish (Pterophyllum scalare) - Millán-Ocampo, Laura (2012)
Eugenol (clove oil) has been widely used as an anaesthetic in fishes due to low induction and recovery times. The aim of this study was to assess the anaesthetic concentration of eugenol in 40 angel fish (Pterophyllum scalare) under laboratory conditions. The animals were exposed to four concentrations of eugenol (20, 30, 40 and 50 mg/L). Observations of the anaesthetics induction (phase I, II, and III) and recovery (phase I, II, III, and IV) were registered. The animals exposed to the higher concentrations of eugenol (40 and 50 mg/L) reached in a short time the first induction anaesthetic stage but had the longer recovery time (p<0.05). The 20 mg/L concentration of eugenol induce light anaesthetic stage in angel fish (phase I) while the 50 mg/L concentration induce an advanced stage of anaesthetic (III). The most effective concentration was 40 mg/L of eugenol for angel fish.